From hypertext to interactive narrative: structure, agency, and multimodal meaning-making of e-literature - Nurmalita Herdiana (Lingua Technica: Journal of Digital Literary Studies, 2025)
Background: The expansion of digital culture has transformed literature from a print-based, linear, and author-centered form into a computational, multimodal, and interactive system of meaning-making. Objective: This study aims to examine the evolution of electronic literature from hypertext fiction to interactive narrative by analyzing how textual structure, reader agency, and multimodal experience change across selected digital literary forms. Method: Using a qualitative digital humanities design, the study analyzes selected works and metadata from curated electronic literature archives, including the Electronic Literature Collection, ELMCIP Knowledge Base, The NEXT, and Pathfinders, through hypertextual structure analysis, interactive narrative analysis, and multimodal discourse analysis. Results: The findings show that early hypertext fiction replaces linear sequence with nodes, links, lexias, screens, and navigational pathways that reposition the reader as an active explorer of textual architecture. Implication: This study also reveals that interactive narrative expands reader agency from pathway selection into decision-making, action, feedback, interface-mediated participation, and narrative consequence within responsive story systems. Novelty: The novelty of this study lies in its integrative analytical model that connects hypertextual architecture, participatory agency, and multimodal transformation as three interrelated dimensions in the evolution of electronic literature.